ANALYSIS FINANCIAL RATIOS ON FINANCIAL DISTRESS OF TRANSPORTATION COMPANY LISTED ON INDONESIAN STOCK EXCHANGE IN 2017-2020 PERIOD - Inggamal, Amelia (Universitas Muhammadiyah Yogyakarta, 2022)
This study wants to see and analyze how the business and financial conditions of transportation companies affected by the covid-19 pandemic using financial ratios measured by CR, DER, ROA, and TATO, which are strengthened in the use of the Altman Z-Score Method as a detector financial distress. The method of this research using altman z-score to predict financial distress with financial ratios and also the data analyze with logistic regression. The result we can find and analyze the effect of liquidity ratio (CR), leverage ratio (DER), profitability ratio (ROA) and activity ratio (TATO) on financial distress condition in transportation company that listed on the Indonesia Stock Exchange for the study from 2017-2020. This study aims to determine the effect of financial ratios, namely the liquidity ratio as measured by the Current Ratio (CR), the leverage ratio as measured by the Debt Equity Ratio (DER), the profitability ratio as measured by Return On Assets (ROA) and the activity ratio as measured by Total Assets Turnover (TATO) on financial distress conditions in transportation companies listed on the Indonesia Stock Exchange for the study period from 2017-2020. So, based on the results of the logistic regression that has been carried out in this study, Liquidity Ratio measured using the Current Ratio (CR) has a positive effect in predicting financial distress conditions, Leverage ratio as measured by using the Debt Equity Ratio (DER) has no effect in predicting financial distress, Profitability ratio as measured by using Return On Assets (ROA) has no effect in predicting financial distress in transportation companies listed on the Indonesia Stock Exchange, and Activity ratio as measured using Total Assets Turnover (TATO) has a positive effect in predicting financial distress.